The approach towards the ball, rather than the physical characteristics of the kicker, limits accurate rugby place kicking range: Submission type: Original article. Issue 1 (2nd January 2022) - Atack, Alexandra C.; Trewartha, Grant; Bezodis, Neil E.
ABSTRACT: The aim of this study was to understand how a place kicker's range is limited by their approach to the ball and their physical characteristics. Thirty-three kickers performed maximal place kicks and vertical jumps in a laboratory. Whole-body motion and ground reaction forces during the approach phase of the kicks, jump performance and anthropometric measurements of those whose predicted maximum distance was limited by range (n = 17) rather than accuracy were analysed. Principal component analysis (PCA) reduced the number of variables considered before stepwise regression analyses assessed variance in place kick maximum distance and associated criteria. Four components, explaining 94% of the variance in maximum distance, were extracted from the PCA: width of approach, anterior-posterior body position, centre-of-mass height and lower limb strength. Lower limb strength was a significant predictor of both kicking foot velocity ( R 2 = 0.55, p = 0.001) and ball velocity magnitude ( R 2 = 0.57, p < 0.001). However, maximum distance was determined by body position during the approach (antero-posterior position, R 2 = 0.52, p = 0.001 and centre-of-mass height, R 2 = 0.12, p = 0.049). This highlights the importance of considering three-dimensional motion of the kicker alongside their physical capabilities to understand place kicking range.